2009
DOI: 10.1080/00015458.2009.11680537
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the Left Renal Vein A Report of a Case

Abstract: Only a few cases of leiomyoma of the vena cava or iliac vein and, according to our knowledge, only one case of renal vein leiomyoma have been reported. We report a patient with leiomyoma of the left renal vein. Tumour resection was performed by resecting a part of the vein along with the tumour and by ligation of the vein. Left kidney drainage was established through the preserved ovarian vein. In order to establish a diagnosis, careful pathologic examination of multiple sections has to be done and because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Vascular leiomyomas are further classified as capillary angioleiomyomas, cavernous type or venous angioleiomyomas [6]. Among a few hundred cases of venous smooth muscle tumours described in literature, majority are leiomyosarcomas that originate in the Vena Cava [7]. Currently, the differential diagnosis between leiomyoma and leiomyosarcoma is only histopathological after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular leiomyomas are further classified as capillary angioleiomyomas, cavernous type or venous angioleiomyomas [6]. Among a few hundred cases of venous smooth muscle tumours described in literature, majority are leiomyosarcomas that originate in the Vena Cava [7]. Currently, the differential diagnosis between leiomyoma and leiomyosarcoma is only histopathological after surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…But they can grow along the vein wall and spread within its lumen in a downstream direction which can lead to thrombosis. Hence, the recommended procedure is excision of the mass and ligation of the feeder vessels [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zelić et al reported a patient with leiomyoma of the left renal vein in 2009. Tumour resection was performed by resecting a part of the vein along with the tumour and by ligation of the vein [ 13 ]. Kefeli et al reported a 52-year-old man with leiomyoma of the left renal vein in 2009.…”
Section: Discussionmentioning
confidence: 99%